Lower Bounds of the Resolvent Estrada Indices for Line Graphs and Complementary Graphs
Let G be a simple graph of order n. The resolvent Estrada index of G is defined as REE(G)=_i=1^n n-1n-1-λ _i , where λ _1 , λ _2 , … , λ _n are the eigenvalues of the adjacency matrix A(G). In this paper, we present several lower bounds of the resolvent Estrada indices for line graphs of any regular graphs and their complementary graphs., number=1, journal=Discontinuity, Nonlinearity, and Complexity, author=Jia, Shuxiang and Deng, Bo and Ye, Chengfu and Liang, Weilin, year=2026, month=Aug., pages=49–55